2016
DOI: 10.1186/s12906-016-1385-5
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic and cytotoxic potentials of compounds isolated from Millettia macrophylla Benth (Fabaceae): towards a better understanding of its underlying mechanisms

Abstract: Background Millettia macrophylla was previously reported to have estrogenic effects and to prevent postmenopausal osteoporosis in Wistar rats. So, the study deals with the identification of its secondary metabolites and the evaluation of their estrogenicity and cytotoxicity toward tumoural cells. Thus, 13 known compounds were obtained from successive chromatographic columns and identified by NMR data compared to those previously reported.MethodsIn vitro estrogenicity of the isolates and the phenolic fraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 59 publications
(74 reference statements)
1
22
0
Order By: Relevance
“…This plant was moderately active against HepG2 cells, providing additional information on the anticancer activity of the plant. The poor cytotoxic effects of compounds and phenolic fractions of M. macrophylla towards breast cancer cells MCF-7 and MDA-MB-231, was reported [26]. Data obtained herein are in accordance with this previous study, as a moderate effect of MML was obtained in MCF-7 cells.…”
Section: Discussionsupporting
confidence: 91%
“…This plant was moderately active against HepG2 cells, providing additional information on the anticancer activity of the plant. The poor cytotoxic effects of compounds and phenolic fractions of M. macrophylla towards breast cancer cells MCF-7 and MDA-MB-231, was reported [26]. Data obtained herein are in accordance with this previous study, as a moderate effect of MML was obtained in MCF-7 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Triterpenoids of M . macrophylla DCM extract were isolated as previously reported (Zingue et al, ). Briefly, 8 g of DCM extract was chromatographed using a normal phase medium pressure liquid chromatography (BÜCHI Labortechnik AG) conditioned in a column with metal sheath glass (36 × 460 mm), adapted to the pressure of work (15 bar).…”
Section: Methodsmentioning
confidence: 99%
“…Twenty‐four hours after the last administration, animals were euthanized by decapitation. The relative uterine wet weight, uterine and vaginal epithelial heights, and differentiation of the mammary gland were assessed as described before by Zingue et al () and Zingue et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Isoflavones, the secondary metabolites of herbal medicine, possess a variety of bioactivities such as antitumor, anti‐inflammatory, antioxidative, antiviral, antibacterial, and estrogenic effects . Recently, metabolites of isoflavones in the human body have aroused great interest due to the potential higher bioactivities, which became one of the most efficient ways for drug discovery . The intestinal flora in the gastrointestinal tract exert an important influence on the in vivo biotransformation of the components in phytomedicines .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the proposed metabolic pathways will be helpful for understanding the in vivo metabolic process of isoflavone.Recently, metabolites of isoflavones in the human body have aroused great interest due to the potential higher bioactivities, which became one of the most efficient ways for drug discovery. [18][19][20] The intestinal flora in the gastrointestinal tract exert an important influence on the in vivo biotransformation of the components in phytomedicines. 21 Previous studies found that the intestinal flora participated in the metabolism of flavones 22,23 and phenolic acids, 24 in which a deconjugating enzyme in bacteria played an important role on the biotransformation of parent compounds to new metabolites with more bioactivities.…”
mentioning
confidence: 99%